Transplanting the United States' style of safe harbour provisions on internet service providers via multilateral agreements: can one size fit all? - Ismail, Suzi Fadhilah; Abdul Ghani Azmi, Ida Madieha; Daud, Mahyuddin (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
Ideally, internet service providers (ISP) should not be burdened with policing contents that pass through their services as they have no editorial control over them. The United States Digital Millennium Copyright Act 1998 (DMCA) changes the ball game by making it mandatory on ISPs to take down infringing copyright materials if they received a notice and takedown request from a copyright holder. In exchange, the ISPs enjoy safe harbour from any liabilities that might arise from their user's action. Serious efforts are needed to transpose a similar system via negotiations and multilateral treaties and agreements involving a number of countries such as through the Trans-Pacific Partnership (TPP) Agreement. Despite the withdrawal of the United States’ (US) from the TPP, and in view of the global initiatives of harmonization of intellectual property (IP) laws, this article aims to explore the different system of ISPs’ obligations and liabilities in the twelve TPP member countries. It also examines some of the strengths and weaknesses of each system. It concludes with an argument that whilst some form of safe harbour should be created to assist IP right owners in policing their right, the US private notice and takedown system is not without its flaws and hence, other existing systems which are adopted in some of the TPP member countries are equally feasible and serve a common purpose in tackling the issue of copyright infringement vis-à-vis ISP liability. Eventually, there is no compelling reason to impose one single system on all the TPP member countries to police the internet via ISP liability.